Asymmetric impact of stokvel and banking sector efficiency in South Africa: Evidence from non-linear ARDL approach - Lindiwe Ngcobo (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
This study examines the impact of stokvel savings and banking sector efficiency in South Africa using the non-linear autoregressive distributed lag (NARDL) bound testing approach technique with economic time series data ranging from 2009Q4 to 2020Q2. The NARDL results shows that positive and negative shocks on banking sector efficiency exhibited a positive influence on stokvel savings. An improvement in banking sector efficiency would result in an increase in stokvel savings of approximately 0.33%, while a decline in banking sector efficiency would lead to increase in stokvel savings albeit at a marginally reduced level of approximately 32%. The results are statistically significant at 1% and 5% for a positive shock and a negative shock respectively. Insignificant results obtained when using gross domestic product growth as dependent variable. This implies that the N-ARDL is not an appropriate model for estimating GDPG. Statistically significant results were found at 5% when using money supply.